Beyond cholesterol: Exploring serum ferritin’s and high-sensitivity C-reactive protein role in cardiovascular risk - Goda, Veena Murthy; Pramodini Garikipati,; Jyothi Nunna, (Asian Journal of Medical Sciences, 2024)
Background: Iron, a pivotal element in the oxidation of low-density lipoprotein (LDL) cholesterol, exerts influence on inflammatory responses and exhibits a positive association with coronary heart disease. Elevated levels of the inflammatory marker, C-reactive protein (CRP), serve as a predictive risk factor for subsequent cardiac events. Aims and Objectives: This study explores the interplay between cardiovascular disease risk factors and serum ferritin concerning CRP. Materials and Methods: A cohort of 750 subjects (375 males and 375 females) was subjected to analysis. Elevated levels were defined as CRP >3.0 mg/L, serum ferritin >200 ng/mL, total cholesterol >200 mg/dL, and LDL-cholesterol >160 mg/dL. HDL cholesterol levels below 40 mg/dL were categorized as low. Results: Within the low LDL-cholesterol group, no discernible correlation was observed between serum ferritin and high-sensitivity CRP (hsCRP) (odds ratio [OR] of 54.95, 95% confidence interval [CI] = 0.81–3.48, P<0.148). Conversely, a correlation was identified in the elevated LDL-cholesterol group (OR of 10.98, 95% CI=1.12–111.22, P<0.05). Furthermore, the introduction of an interaction term in the assessment of the correlation between elevated hsCRP and LDL-cholesterol reaffirmed a robust correlation between hsCRP and serum ferritin (P<0.005). Conclusion: The oxidation of LDL-cholesterol by serum ferritin emerges as a potential contributor to inflammatory reactions and heightened hsCRP levels. Prospective studies are warranted to investigate whether interventions targeting the reduction of serum ferritin and CRP levels, through medical interventions and lifestyle modifications, could prove efficacious in preventing cardiovascular diseases.